Comparison of Cable Insulation Control in Weak and Strong Electric Fields; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Starikova N. S. Nadezhda Sergeevna (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen